PENGGUNAAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SEKOLAH DASAR PADA PEMBELAJARAN IPA - 1)Mar’attus Solihah dan 2)Anggraeni Mashinta (Universitas PGRI Yogyakarta, 2019)
AbstractThis study aims to determine the effect of using Problem Based Learning on problem-solving abilities of elementary school students in science learning. The study was conducted in two elementary schools namely Gunungreja Public Elementary School 02 and MI Mafatihul Huda Cipari involving 83 students in the 5th grade. The study design used a non-randomized pretest-posttest design by dividing students in two groups: 42 control group students and 41 treatment group students . The control group is learning the material